Determination of Diffusion Coefficients of Heavy Metal Ions (Ni3+, Zn2+, Ba2+, and Mn2+) at Infinite Dilution through Electrolytic Conductivity Measurements - Dimaculangan, Dianne Aubrey A.; Bungay, Vergel C; Soriano, Allan N. (ASEAN Journal of Chemical Engineering, 2022)
One important parameter to examine the behavior and mass transfer properties of heavy metal ions is the diffusion coefficient. Due to the costly methods of its determination, a simple process correlating the molar conductivity data to diffusion coefficient was utilized. Molar conductivity data were determined for five (5) different dilute concentrations of the chlorides of the heavy metal ions (Ni3+, Zn2+, Ba2+, and Mn2+) and at temperatures ranging from 303.15 to 323.15 K. The infinite dilution diffusion coefficients of the heavy metals were estimated using the Nernst-Haskell equation and Nernst-Einstein equation. The molar conductivity and the diffusion coefficients values of the ions were in the order of Ba2+ > Mn2+ > Zn2+ > Ni3+ with the Ba2+ having the highest molar conductivity with a correlated infinite dilution diffusion coefficient of 1.6565 × 10-9 m2/s at 303.15 K. This study was able to predict the values of the infinite dilution diffusion coefficient of heavy metal ions and could contribute to a better understanding of the mobility of heavy metal ions in a water environment